2005
DOI: 10.1111/j.1439-0418.2005.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal forms and reproductive potential of the common pistachio psylla, Agonoscena pistaciae (Hem., Psylloidea)

Abstract: Two distinct seasonal forms were found for the common pistachio psylla, Agonoscena pistaciae, the most serious insect pest of cultivated pistachio trees, Pistacia vera in Iran. The two forms are different morphologically as well as biologically. The summer form is of light colour and readily mates and starts egg laying 1-2 days after emergence, whereas, the winter form is larger, generally darker and in reproductive diapause. The first form is observed under long photoperiod, while the second form is induced u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…The evolution of pesticide resistance has resulted in chemical applications failing more frequently (Mehrnejad, 2003(Mehrnejad, , 2010(Mehrnejad, , 2014. Laboratory and field studies have documented the biology and ecology of CPP and its natural enemies (Jalali et al, 2014;Kazemi and Mehrnejad, 2011;Mehrnejad, 1998Mehrnejad, , 2008Mehrnejad and Copland, 2005a, 2005b, 2006a, 2006b, 2006cMehrnejad and Emami, 2005;Mehrnejad et al, 2011;Pourali et al, 2012). However, despite the wide range of possible biocontrol agents, none have yet been studied for feasibility of rearing and mass release in an augmentation program.…”
Section: Introductionmentioning
confidence: 97%
“…The evolution of pesticide resistance has resulted in chemical applications failing more frequently (Mehrnejad, 2003(Mehrnejad, , 2010(Mehrnejad, , 2014. Laboratory and field studies have documented the biology and ecology of CPP and its natural enemies (Jalali et al, 2014;Kazemi and Mehrnejad, 2011;Mehrnejad, 1998Mehrnejad, , 2008Mehrnejad and Copland, 2005a, 2005b, 2006a, 2006b, 2006cMehrnejad and Emami, 2005;Mehrnejad et al, 2011;Pourali et al, 2012). However, despite the wide range of possible biocontrol agents, none have yet been studied for feasibility of rearing and mass release in an augmentation program.…”
Section: Introductionmentioning
confidence: 97%
“…Variation in body color has been described in numerous species within the superfamily Psylloidea, including Cacopsylla midoriae (Miyatake) (Inoue 2004); Cacopsylla elegans Inoue (Inoue 2004); Cacopsylla chinensis (Yang & Li) (Yang et al 2004); Agonoscena pistaciae Burckhardt & Lauterer (Mehrnejad and Copland 2005); and the pear psylla, Cacopsylla pyricola (Fö rster) (Wong andMadsen 1967, Krysan andHigbee 1990), as well as in many species in the family Aphididae (Araya et al 1996;Watt and Hales 1996;Miller 1998, 2001;Nevo and Coll 2001;Toros et al 2003). This variation is may be associated with different seasonal forms, endosymbionts (Weisgraber et al 1971, Jenkins et al 1999, or (in some aphids) genetically distinct morphs (Araya et al 1996, Langley et al 2006.…”
mentioning
confidence: 97%
“…Triggers for diapause are likely to be environmental cues, such as photoperiod and temperature. For the few psyllids in which these cues have been examined, photoperiod is an important controlling factor (Wong & Madsen, ; Nguyen, ; Horton et al ., ; Mehrnejad & Copland, ). Laboratory experiments have indicated that, in the case of C. pyricola and C. pyri , the trigger for reproductive diapause in overwintering females is mostly short‐day conditions (Wong & Madsen, ; Nguyen, ; Horton et al ., ).…”
Section: Discussionmentioning
confidence: 99%